Advances in library administration and organization. Vol. 30 - Williams, Delmus Eugene; Golden, Janine (Advances in library administration and organization,, 2011)
As it continues to publish work that is relevant for both researchers and library practitioners, Volume 30 of Advances in Library Administration and Organization contains articles describing efforts at cooperation and collaboration within the library profession. This volume includes scholarship that illustrates both concepts, best defined in one of the chapters as terms "often used loosely to describe relationships among entities or people working together." Topics explored within the volume include an examination of public and academic libraries as places that provide purposeful spaces specific to providing user need fulfilment; library services in juvenile detention centers; and the contribution of school library media specialists. The development of electronic institutional repositories, primarily in academic libraries and based on efforts to encourage campus community involvement and partnerships between librarians and the faculty they serve is discussed. Successful fund raising in libraries is explored through the examination of the impact of organizational placement of the library development officer in universities.